1999
DOI: 10.1103/physrevb.59.46
|View full text |Cite
|
Sign up to set email alerts
|

General localization lengths for two interacting particles in a disordered chain

Abstract: The propagation of an interacting particle pair in a disordered chain is characterized by a set of localization lengths which we define. The localization lengths are computed by a new decimation algorithm and provide a more comprehensive picture of the two-particle propagation. We find that the interaction delocalizes predominantly the center-of-mass motion of the pair and use our approach to propose a consistent interpretation of the discrepancies between previous numerical results. PACS number(s): 72.15. Rn,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 12 publications
(36 reference statements)
2
32
0
Order By: Relevance
“…Numerical results in one dimension [6], although in line with the sign-independence, do not fully support the U 2 dependence predicted analytically. Moreover, the effect is numerically found to be strongest when the two electrons move at short distance [9], a feature which is also not covered by the analytical expression. Finally, the result (1) has either been derived heuristically [2], or it is based on statistical assumptions [8] which, although plausible, are not obviously valid.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Numerical results in one dimension [6], although in line with the sign-independence, do not fully support the U 2 dependence predicted analytically. Moreover, the effect is numerically found to be strongest when the two electrons move at short distance [9], a feature which is also not covered by the analytical expression. Finally, the result (1) has either been derived heuristically [2], or it is based on statistical assumptions [8] which, although plausible, are not obviously valid.…”
Section: Introductionmentioning
confidence: 81%
“…The numerical work of Ref. [9] in one dimension has clearly demonstrated that the change of the localization length caused by the two-body interaction is biggest when the two electrons which move through the one-dimensional wire, keep the shortest distance from each other. This is our motivation for the constraint artificially imposed in our model.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations